Evaluation of vegetative barriers for runoff, soil loss and crop productivity in Kandi region of Punjab - SINGH, M. J.; YOUSUF, ABRAR; SHARMA, S. C.; BAWA, S. S.; KHOKHAR, ANIL; SHARMA, VIVEK; KUMAR, VIJAY; SINGH, SATVINDER; SINGH, SHER (Journal of Soil and Water Conservation, 2020)
An experiment was conducted for eight years to evaluate the effect of five vegetative barriers namely Vetivar grass (Vetiveria zizanoides), Bhabbar grass (Eulaliopsus binata), Kanna grass (Sachharum munja), Subabul (Leucaena leucocephala) and Napier bajra hybrid (Pennisetum purpureum X typhoides) on runoff, soil loss and crop parameters at the research farm of Regional Research Station (Punjab Agricultural University), Ballowal Saunkhri, Punjab. During kharif season, blackgram, sesame and maize were grown in the top, middle and bottom section of plots and in rabi season wheat, raya and lentil were grown in the top, middle and bottom section of plots, respectively. The runoff and soil loss was significantly reduced under the vegetative barriers as compared with control. Among the different vegetative barriers, kanna and napier bajra hybrid were found to be most effective in controlling runoff and soil loss. The average runoff generated through the kanna and napier bajra hybrid was only 10.8% and 15.8% and the soil loss measured was 4.56 and 5.01 Mg ha-1 respectively. During kharif season, among different vegetative barriers, kanna proved best followed by napier bajra hybrid and bhabbar in terms of yield of maize, sesame & black gram, water use efficiency and economics. The percent increase in the yield of maize, sesame and black gram in kanna grass as compared to control treatment was found to be 31.8%, 30.5% and 30.8% respectively. During rabi season, the effect of vegetative barriers on yield and yield attributes of all tested crops was non-significant.